Human capital as an important factor in the growth of the country. (Journal of Economic Research & Business Administration, 2015)
In this article to the opening of the importance of human capital to join the ranks of developed countries in the world . The experience of developed countries in the level of human capital and socio-economic development depends on that . Author of human capital by emphasizing the role of the states in some course of action .